Pengaruh Prestasi Belajar Antara Mahasiswa Aktif Organisasi dan Tidak Aktif Organisasi pada Mahasiswa Jurusan BKI Fakultas Dakwah dan Komunikasi IAIN Mataram - Nashatun Nashatun (Jurnal Budi Pekerti Agama Islam, 2023)
This research aims to know the "influence of the Liveliness of the students Organize Against the achievements of the Islamic guidance counseling Student Learning Force 2014". The approach used is a quantitative approach with insrumen data collection in the form of the now closed terdidri of 15 items, tested the validity of the statement and realibilitasnya. Data that has been collected and then analyzed using analytical statistics using statistical analysis with data processing statistical instruments product and service solution (SPSS). The location of the research conducted on campus one IAIN Mataram total population of 479. The large amount of samples taken from the population is 60 Students 10% calculated using the formula sample Probability Sampling. The result of the processing of research data shows that the student has freedom of activity variables influence the learning achievements of students Islamic Forces 2014 guidance counseling. To answer the problem formulation and hypothesis testing studies have been done of t and F test results obtained by using the SPSS program was Active Student Association Student Learning Achievements to guidance counseling. Where the value of the t-female 6.1782 > t-2.048. This shows (Ha) in the receive and (Ho) in decline. keduan variable to see whether it has the influence of learning achievements against simultaneously Students Islamic guidance counseling, then do the test F. And hasinya shows a value of F Count i.e. < 1.7057 1.8608 with probalitas signifikasinya 0.000. The probalitas value smaller than 0.05 Ha berakti are accepted and rejected, in the language of the Ho whose hypotheses Liveliness Students Organize the learning achievements of Students to Counseling Guidance Islam Forces 2014.